Rekonsiliasi Hubungan Sunni-Syiah di Kawasan Timur Tengah - Wibowo, Prihandono; Zamzamy, Ahmad (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2015)
War based on Sunni and Shia identity becomes a trend in contemporary conflicts in the Middle East. Unlike the Sunni-Shia conflict in the classic period as a result of theological dispute, the current conflict between the two groups are more influenced by political, economic and social variables. Therefore, it is necessary to analise the Sunni-Shia conflict comprehensively. The analysis provides steps to reconcile relations between Sunni-Shiite in the contemporary period. Reconciliation can be strengthened through dialogue among Sunni-Shia, construct common enemy and open socio-political access.